A Novel Method for the Chlorolactonization of Alkenoic Acids Using Diphenyl Sulfoxide/Oxalyl Chloride - Ding, Rui; Lan, Liyuan; Li, Shuhui; Liu, Yongguo; Yang, Shaoxiang; Tian, Hongyu; Sun, Baoguo (Synthesis, 2018)
A facile chlorolactonization of alkenoic acids by treatment with diphenyl sulfoxide/oxalyl chloride has been developed. The reaction can generate various chlorolactones in moderate to good yields, wherein the chlorodiphenylsufonium salt derived from diphenyl sulfoxide/oxalyl chloride serves as the source of Cl+.
Keywords: chlorolactonization; alkenoic acids; diphenyl sulfoxide; oxalyl chloride; chlorodiphenylsulfonium salt